Implementasi Optical Character Recognition (OCR) Pada Masa Pandemi Covid-19 - Ali Firdaus; M. Syamsu Kurnia; Tia Shafera; Wahyu Istalama Firdaus (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Abstract Many documents must be processed and scanned digitally, especially during this pandemic, physical documents often have to be reprocessed using word processing applications. This process takes a lot of time especially if the document is damaged, lost and does not have a copy. This can be overcome by using the Optical Character Recognition (OCR) algorithm. OCR converts letter images into computer-recognized ASCII characters. Image files are relatively larger than their ASCII text files. From the existing problems, the researchers tried to find a solution by creating an OCR application program to simplify the process. The created OCR program is successfully used to scan or scan a physical document if the document is lost or damaged, and can save time on document creation, processing and typing. Keywords: Algorithm, Optical Character Recognition, ASCII